Systemic Lupus Erythematosus Prevalence in Sweden in 2010: What Do National Registers Say?. Issue 11 (November 2014) - Simard, Julia F.; Sjöwall, Christopher; Rönnblom, Lars; Jönsen, Andreas; Svenungsson, Elisabet
<x xml:space="preserve">Abstract</x> Objective Worldwide prevalence estimates of systemic lupus erythematosus (SLE) range from 3 to 207 per 100, 000, depending on region and population, SLE definition, case sources, and other methodologic considerations. We aimed to determine the prevalence of SLE in Sweden on January 1, 2010, using population‐based registers. Methods Linking multiple national registers, we identified all possible inpatient and outpatient visits with SLE‐specific discharge diagnoses and relevant prescription dispensations among living individuals registered in Sweden on January 1, 2010. SLE was defined from a lenient classification (requiring only a single visit) to stricter definitions that required multiple visits with a history of relevant specialist care and a dispensation for common SLE medications. Prevalence was calculated overall and by sex, age (0–14 years, 15–49 years, and ≥50 years, as well as in 5‐year age groups), and county of residence. Results Overall prevalence ranged from 46 per 100, 000 for the strictest definition to 85 per 100, 000 for the least strict definition. As expected, SLE was more common among females (range 79–144 per 100, 000) than males (range 12–25 per 100, 000) and varied by age. The up to 4‐fold variation by county was unexpected. Prevalence generally increased with age (2, 52, and 95 per 100, 000 by increasing age group, 0–14 years, 15–49 years, and ≥50 years, respectively, using a moderately strict definition) and also varied by county. Conclusion Variations of prevalence by age and sex were consistent with previous studies and overall ranged from 46 to 85 per 100, 000. We observed a surprising geographic variation in the prevalence of SLE in Sweden on January 1, 2010, according to multiple definitions.